Capital Market Development and Nigerian Economy - Binuyo, Babatunde O.; Oluwatimilehin, Durojaiye; Edy-Ewoh, Uduakobong; Binuyo, Adekunle O. (NIU Journal of Social Sciences; Vol 5 No 2 (2019): KIU Journal of Social Sciences, Vol. 5 No. 2, June 2019, 2019)
This research work examined the effects of capital market development on the Nigerian economy from 1987 to 2018. Most recent literatures on the Nigeria capital market have recognized the tremendous performance the market has recorded in recent period. However, the vibrant role of the capital market in economic development has not been empirically investigated thereby creating a research gap in this area. This study was motivated by the fact that some studies have reported negative effects of capital markets on economic growth in some developing nations instead of positive effect on growth and development. Ex-post-facto research design was adopted for the study. The study used time series data, and, the ordinary least squares technique was adopted for analysis. The result showed that market capitalization has a positive influence on the gross domestic product (GDP) while value of transactions has a negative and insignificant influence on GDP. Based on the findings, the study recommends that Government should encourage participation of foreign investors in the capital market, and a lasting solution should be found to control the current state of insurgency in the North-Eastern part of the country. Major instruments such as derivatives, convertibles, future and Swaps-options among others could be introduced to enhance the development of the capital market. Keywords: Capital market, , Economy, , Foreign investors, Gross domestic product, Market capitalization